Water budget-salt balance model for calculating net water saving considering different non-conventional water resources in agricultural process - Danboos A.; Sharil S.; Mohamad Hamzah F.; Yafouz A.; Huang Y.F.; Ahmed A.N.; Ebraheem A.A.; Sherif M.; El-Shafie A. (Elsevier Ltd, 2024)
Iraq is facing a dire water crisis due to the decrease in water quantities flow in Tigris and Euphrates Rivers. Due to population growth, several studies estimated the water shortage in 2035 to be 44 Billion Cubic Meter (BCM). Thus, Water Budget-Salt Balance Model (WBSBM) has been developed, applied and examined for the Euphrates River basin to compute the net water saving from Non-Conventional Water Resources (NCWRs). WBSBM includes 4-stages